Evaluating Blockchain Success: Integrating Organizational Decentralization with the DeLone and McLean IS Success Model - Lashkari, Alireza (2021)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Information Systems and Technologies Management